Optimalisasi Pengelolaan Keuangan melalui Digitalisasi Pencatatan pada Usaha Mikro dan Kecil - Misriati, Titik; Setyaningsih, Eka Dyah; Aryanti, Riska (Forum Kerjasama Pendidikan Tinggi, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in driving the local economy, including in the city of Bekasi. However, the main challenge faced by MSME players is their low capacity to manage and record finances effectively. Most business owners still use manual recording methods, which risk errors, data loss, and difficulties in analyzing financial conditions. In addition, the lack of separation between business and family finances causes uncertainty in profit and loss calculations and capital planning. The lack of knowledge about the use of digital financial applications is also a significant obstacle. This community service activity aims to empower MSMEs in Bekasi City to move up the ladder through digital innovation in financial recording. The partners in this activity are MSMEs in the Bekasi City area that have not yet implemented a digital recording system. The implementation method includes stages of needs analysis, financial literacy training, assistance in using digital recording applications, and evaluation of the level of understanding through pre-tests and post-tests. The results of the activity show an average increase in understanding and application of digital financial management of 80%. Business owners have become more disciplined in recording transactions, able to separate business and personal finances, and understand profit and loss calculations more accurately. In addition to its economic impact, this activity has also fostered social change in the form of the Bekasi Digital MSME community, which serves as a platform for continuous learning. Digital innovation has proven effective in increasing the professionalism and competitiveness of MSME players towards a technology-based economic transformation.